RANCANG BANGUN SISTEM INFORMASI SISWA BERBASIS WEB DI SEKOLAH MINGGU BUDDHA VIHARA DHARMALOKA PEKANBARU - Andrianto, Sukrisna; Wijoyo, Hadion (TIN: Terapan Informatika Nusantara, 2020)
The development of information systems so rapidly that it is possible to do data processing that saves time and money while still producing information that is very accurate and useful. This can support the success of a school or organization in achieving its goals. One of the data processing that needs to use a computerized system is the design of a web-based information system for the Buddhist Sunday School in the Dharma Loka Pekanbaru Temple. The design of the web-based information system of the Buddhist Sunday School in Vihara Dharma Loka has not used a lot of computer-based information systems. This school still uses a manual system, data entry still uses Microsoft Excel such as new student registration, inputting student data, teacher data, student assessment, student attendance, minutes, announcements to students and teachers, and report data. Design a web-based information system for the Buddhist Sunday School at Vihara Dharma Loka using the PHP programming language with a MySQL database. The application design is expected to make it easier to access the data of the Buddhist Sunday School at Vihara Dharma Loka and present the information quickly and more effectively and efficiently